IDENTIFIKASI SALURAN INFORMASI PEMASARAN PERIKANAN SEBAGAI BAGIAN DARI PENGEMBANGAN SISTEM INFORMASI PEMASARAN PERIKANAN - Etik Sulistiowati Ningsih; Oon Darmansyah; Erwiantono . (Metacommunication, 2018)
Development of fisheries marketing information system which have been done by Fisheries Department is a kind of effort to provide marketing information for all of stakeholders within marketing channel. Its aims to reduce information asymmetry of fisheries marketing. As an innovation, such information system must be disseminated through appropriate communication channel. This article was written based on primary data sources gained by interviewing on perception of fish cage farmer to communication channel used to get marketing information. This research demonstrate that the most frequent communication channel used to get marketing information is personal communication channel.Keywords:  Information channel, fisheries marketing, information system.